2018
DOI: 10.1177/0972150918794977
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sales Promotion’s Benefits on Brand Equity: An Empirical Investigation

Abstract: Sales promotion is known for providing additional benefits to the consumers and these benefits may have an impact on the development of consumer-based brand equity. Although previous studies have reported a positive influence of sales promotion on brand equity, but the impact of sales promotion’s benefits (i.e., hedonic and utilitarian benefits) on brand equity is less understood. This study examined the possible influence of sales promotion’s hedonic and utilitarian benefits on four components of brand equity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
2
12
0
2
Order By: Relevance
“…Without a doubt a first conclusion is that the world shipyards should rethink their strategies in the dimensions of Sales promotion and Sponsorship, where it is proven in other sectors that can be very beneficial for them and improve their competitiveness and global performances. 45 Concerning the dimensions of Advertising, Direct Marketing and Public Relations, a variation of the data obtained in the different shipyards is identified, so it is necessary to carry out a comparative analysis, similar to the one that was carried out previously with the Marketing Promotion Index. In this way, Figure 7 is shown, representing the relationship between these three dimensions and the performances related to the variation of the shipyard's orderbook over the last 3 years, and Figure 8 with the variation of the shipyard's new orders over the last 3 years.…”
Section: Resultsmentioning
confidence: 99%
“…Without a doubt a first conclusion is that the world shipyards should rethink their strategies in the dimensions of Sales promotion and Sponsorship, where it is proven in other sectors that can be very beneficial for them and improve their competitiveness and global performances. 45 Concerning the dimensions of Advertising, Direct Marketing and Public Relations, a variation of the data obtained in the different shipyards is identified, so it is necessary to carry out a comparative analysis, similar to the one that was carried out previously with the Marketing Promotion Index. In this way, Figure 7 is shown, representing the relationship between these three dimensions and the performances related to the variation of the shipyard's orderbook over the last 3 years, and Figure 8 with the variation of the shipyard's new orders over the last 3 years.…”
Section: Resultsmentioning
confidence: 99%
“…A study performed by Akhtar et al (2016) showed that brand association has less impact on brand equity than brand loyalty. While the study performed by Sinha and Verma (2018) revealed that the utilitarian advantage of the advertisement has the most impact on brand loyalty, while the hedonic advantage of the advertisement has the most impact on brand association. Mudanganyi et al (2019) revealed that to succeed and survive, the service providers need to build brand equity because it ensures customer retention, repeat purchase and association.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 96%
“…consumers' familiarity with and awareness of brands (Datta et al, 2017). In-store sales promotions are one method whereby retailers can improve brand identification, and thereby can raise the brand equity of a product (Sinha and Verma, 2018). Sales promotions are not only effective tools for increasing sales but can be used to develop relationships with customers, enhancing consumers attitudes and loyalty towards a brand (Palaz on-Vidal and Delgado-Ballester, 2005;Mussol et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%